TASKS OF MODERN LINGUISTIC TYPOLOGY AND CONTRASTIVE LINGUISTICS (on the example of comparing Spanish and Ukrainian languages) (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
When comparing the native language and a foreign language, several methods of comparison are used, which differ significantly from each other. Therefore, the disciplines that deal with the comparison of two or more languages are multilingual, they are based on cross-linguistic comparison. Comparative-historical, areal, and typological research aims to build appropriate classifications of languages, they are aimed at finding similar features in the compared languages that connect them and form the basis for genetic correspondences, which is explained by primary linguistic affinity. Contrastive linguistics is mainly interested in what distinguishes the languages being compared, and what may be a factor causing cross-linguistic interference. Comparative typology and congruent linguistics, not being interested in the genetic origin of languages, their diachronic development, have their specific goals, purpose, research material and limits of application. If comparative typology pays attention primarily to similar features between two languages, then contrastive linguistics focuses on identifying differences in order to prevent mistakes when learning foreign languages.__________References:• http://yazykoznanie.ru>content>view• https://p-tashka.livejournal.com>• Korunets, Ilko Contrastive Typology of the English and Ukrainian Languages (Vinnitsya, 2004).• Kochergan, M. P. Zagal'ne movoznavstvo (2006), https://irbis-nbuv.gov.ua• Antonio, Blázquez Ortigosa. La lingüística contrastiva como método de enseñanza en el aula de inglés (2010).• Mercé, Tricás Preckler. «Lingüística Contrastiva y Traducción. Aproximaciones interculturales.» Synergies Espagne3 (2010):13-22.
Keywords: Linguistic typology, comparative research method, contrastive linguistics